Model Pendampingan Ekonomi Pesantren Berbasis Maqasid al-Shariah untuk Mewujudkan Kemandirian Santri - Abdul Halim; Faiz Faricha (https://journal.metanusantara.com/impact/index.php/jpk, 2026)
Islamic boarding schools as the oldest Islamic educational institution in Indonesia face the challenge of transformation from institutions that depend on donations to independent economic entities, but the reality shows that economic management and student empowerment are still weak. This research aims to develop a model of economic assistance for Islamic boarding schools based on Maqasid al-Shariah that is effective in realizing the independence of students. The research uses a Participatory Action Research (PAR) approach with the active participation of kyai, pesantren administrators, and students in three Islamic boarding schools in East Java and West Java. Data were collected through participatory observation, in-depth interviews, focus group discussions, and documentation. The results of the study show three main findings. First, the mentoring model developed integrates the five dimensions of Maqasid al-Shariah (maintenance of religion, soul, intellect, descent, and property) into the entire mentoring cycle and has been proven to increase business unit revenue by an average of 45% and student participation from 15% to 72%. Second, before the mentoring, the contribution of business units to pesantren operations was only 23% and the entrepreneurial literacy of students was at a score of 42, but after three cycles of PAR there was a significant increase in all indicators. Third, the success of the implementation of the model is determined by the commitment of the kyai and the availability of resources, while obstacles such as limited capital and low financial literacy are overcome through intensive mentoring. The research concludes that the Maqasid al-Shariah-based mentoring model is effective in increasing the independence of students and contributing to the development of the Islamic economy as well as practical guidance for sustainable Islamic boarding school economic management.